Improving the imaging contrast of 68Ga-PSMA-11 by targeted linker design: charged spacer moieties enhance the pharmacokinetic properties - Eder, Ann-Christin; Liolios, Christos; Mier, Walter; Haberkorn, Uwe; Eisenhut, Michael; Kopka, Klaus; Eder, Matthias (Bioconjugate chemistry, 2017)
68Ga-Glu-urea-Lys-(Ahx)-HBED-CC (68Ga-PSMA-11) represents a successful radiopharmaceutical for PET/CT imaging of prostate cancer. Further optimization of the tumor-to-background contrast might significantly enhance the sensitivity of PET/CT imaging and the probability of detecting recurrent prostate cancer at low PSA values. This study describes the advantage of histidine (H)/glutamic acid (E) and tryptophan (W)/glutamic acid (E) containing linkers on the pharmacokinetic properties of 68Ga-PSMA-11. The tracers were obtained by a combination of standard Fmoc-based solid-phase synthesis and copper(I)-catalyzed azide-alkyne cycloaddition. Their 68Ga complexes were compared to the clinical reference 68Ga-PSMA-11 with respect to cell binding, effective internalization, and tumor targeting properties in LNCaP-bearing balb/c nu/nu mice. The introduction of (HE)i (i = 1-3) or (WE)i (i = 1-3) into PSMA-11 resulted in a significantly changed biodistribution profile. The uptake values in kidneys, spleen, liver, and other background organs were reduced for (HE)3 while the tumor uptake was not affected. For (HE)1 the tumor uptake was significantly increased. The introduction of tryptophan-containing linkers also modulated the organ distribution profile. The results clearly indicate that histidine is of essential impact in order to improve the tumor-to-organ contrast. Hence, the histidine/glutamic acid linker modifications considerably improved the pharmacokinetic properties of 68Ga-PSMA-11 leading to a reduced uptake in dose limiting organs and a significantly enhanced tumor-to-background contrast. Glu-urea-Lys-(HE)3-HBED-CC represents a promising 68Ga complex ligand for PET/CT-imaging of prostate cancer.